A qualitative exploration of lymphoma survivors' unmet needs - Boland, Vanessa; Drury, Amanda (My University, 2023)
Background: Lymphoma survival has significantly improved over recent decades. Yet, survivorship research has received little attention. This study aimed to understand the unmet needs experienced by lymphoma survivors through semi-structured interviews. This qualitative study investigates the individual experiences and complexities of lymphoma survivors’ unmet needs. This insight can provide a voice to lymphoma survivors, which is especially valuable for this group as an underserved population in current literature. Methods: A semi-structured interview guide was informed by the findings of a cross-sectional survey study and a literature review conducted by the authors. The findings were derived from interviews with 14 adult survivors about their unmet needs due to lymphoma and responses from 61 participants to an open-ended survey question. A reflexive thematic analysis was conducted to identify themes and patterns of meaning across both datasets (Braun & Clarke 2019). Results: Three major themes were identified. Survivors shared experiences of navigating the complexities of lymphoma, including difficult diagnosis, limited awareness of lymphoma as a cancer and challenges specific to younger adults. Survivors experienced complex care coordination, including disjointed cancer care, physical health concerns and the immunocompromised nature of lymphoma, particularly during the pandemic. The cost of cancer found challenges in balancing life responsibilities with lymphoma, difficulties during the survivorship phase, and dealing with psycho-social problems. Conclusions: Unaddressed unmet physical needs contributed to unmet psychological needs due to the uncertainty experienced by survivors on their quest for answers to health concerns. Psychological and emotional needs were dominant and persistent problems in the survivorship phase one to five years post-diagnosis. Unmet practical and information needs were experienced from disjointed cancer care coordination; a missing link was reported by individuals with lymphoma acting as a conduit for information regarding their cancer. Navigating lymphoma from diagnosis to survivorship presents challenges for patients and healthcare professionals who would benefit from enhanced lymphoma awareness and research.
Annals of Oncology
EONS16 at ESMO
PUBLISHED
Madrid, Spain
Keywords: Cancer; CANCER; Cancer Survivorship; haematological malignancy; unmet needs